Factors Influencing the Establishment of Clothing Retailers in the Metaverse: The Role of Metaverse Technology as a Mediator - Alayli, Sahar (2023)
The metaverse is a virtual environment where people may interact with one another via avatars. As the metaverse has gained in popularity over the last several years, the retail industry has indicated an interest in using it for product promotion and sales. However, opening a clothes store in the metaverse has unique challenges, and prospective investors should keep a few things in mind. This study aimed to uncover the factors that led Dubai investors to create a virtual apparel brand for sale online. Independent factors were creativity, safety, and confidentiality. The advent of Dubai's Metaverse clothes store was the dependent variable, while the technology enabling the metaverse was the mediator. The study used a quantitative methodology, including a survey questionnaire. For demographic and structural equation modeling objectives, we employed SPSS and AMOS software. The mediator variable was shown to be significantly affected by all independent factors, according to data from a survey of 398 participants. The successful debut of apparel in the metaverse in Dubai may be primarily attributed to the metaverse's cutting-edge technological innovations in security and privacy. Customers may be unwilling to provide personal information or engage in virtual transactions if they do not trust the safety of their data in the metaverse; thus, these issues must be addressed. Investors should prioritize developing private and secure metaverse technologies to win users' confidence. The findings call attention to the absence of study in this area and provide valuable insight into the factors contributing to the success of retail clothes launches in the metaverse. When taken as a whole, this study paves the way for more investigation into the metaverse and its possible implications on the retail industry in Dubai.